A Systematic Literature Review of Interoperability in Healthcare Using FHIR - Madhu Gottumukkala (Journal of Systemics, Cybernetics and Informatics)

(untitled)
Despite the available modern technologies, we live in a "fragmented" healthcare system, in which data is stored in multiple sources and a variety of formats and standards without direct communication. However, in the upcoming years, interoperability is emerging, defined as the ability of different information systems, devices, or applications to connect within and across organizational boundaries to access, exchange, and cooperatively use data amongst physicians and patients. We conducted our study using two databases, PubMed and Web of Science, to explore Fast Healthcare Interoperability Resources (FHIR) standard and how we can use FHIR technology to improve interoperability and exchange data between different hospital services. We also expect to find purposes for further research.